Improved Accuracy of Multidimensional Spatially‐Selective Saturation RF Pulses for Short‐Repetition‐Time Steady‐State Imaging - Yongli He; Douglas C. Noll; Jon‐Fredrik Nielsen (Magnetic Resonance in Medicine, 2026)
ABSTRACT Purpose To introduce and evaluate a novel RF pulse design algorithm for multi‐dimensional spatially tailored excitation that is optimized for spoiled steady‐state gradient echo MRI sequences. Methods Existing multi‐dimensional RF pulse design algorithms optimize RF and gradient waveforms using a loss function based on a single RF pulse application. These designs are poorly suited for steady‐state MRI sequences where RF pulses are spaced only tens of milliseconds apart, causing potentially large differences between the steady‐state magnetization and the target pattern. We propose a multidimensional RF pulse design algorithm with a loss function based on the steady‐state magnetization of a spoiled gradient‐echo sequence. Our algorithm, steady‐state AutoDiffPulses (SS‐ADP), extends the previously introduced ADP framework for joint RF and gradient pulse design. We evaluated design accuracy and RF energy in phantom and in vivo brain imaging in inner‐volume (IV) and outer‐volume (OV) saturation experiments. We further evaluated the potential of SS‐ADP to improve reduced FOV (rFOV) imaging. Results SS‐ADP produced significantly more accurate steady‐state magnetization patterns compared to a conventional single‐excitation design (ADP), with significantly reduced RF energy, for . Furthermore, utilizing SS‐ADP for outer‐volume suppression (OVS) substantially reduced reconstruction error in accelerated rFOV imaging compared to conventional ADP‐OVS. Conclusion A joint RF and gradient pulse design algorithm accounting for steady‐state magnetization evolution significantly improves excitation accuracy and reduces SAR in short‐TR spoiled imaging with .